Comparing the level of bystander effect in a couple of tumor and normal cell lines - Soleymanifard, Shokouhozaman (Medknow Publications & Media Pvt Ltd, 2012)
Radiation-induced bystander effect refers to radiation responses which occur in non-irradiated cells. The purpose of this study was to compare the level of bystander effect in a couple of tumor and normal cell lines (QU-DB and MRC5). To induce bystander effect, cells were irradiated with 0.5, 2, and 4 Gy of (60)Co gamma rays and their media were transferred to non-irradiated (bystander) cells of the same type. Cells containing micronuclei were counted in bystander subgroups, non-irradiated, and 0.5 Gy irradiated cells. Frequencies of cells containing micronuclei in QU-DB bystander subgroups were higher than in bystander subgroups of MRC5 cells (P < 0.001). The number of micronucleated cells counted in non-irradiated and 0.5 Gy irradiated QU-DB cells was also higher than the corresponding values for MRC5 cells (P < 0.001). Another difference between the two cell lines was that in QU-DB bystander cells, a dose-dependent increase in the number of micronucleated cells was observed as the dose increased, but at all doses the number of micronucleated cells in MRC5 bystander cells was constant. It is concluded that QU-DB cells are more susceptible than MRC5 cells to be affected by bystander effect, and in the two cell lines there is a positive correlation between DNA damages induced directly and those induced due to bystander effect.